THE FAMILY UNIT AS THE PRIMARY FOUNDATION FOR DEVELOPING SOCIO-CULTURAL COMPETENCIES IN CHILDREN - Atamuxamedova Ra’no Fazildjanovna (International Journal of Innovations in Engineering Research and Technology, 2026)
This article examines factors such as socio-economic status, parents’ level of education, cultural values, and family involvement, which influence the process of developing socio-cultural competence of Uzbek learners.